2001
DOI: 10.1074/jbc.m006917200
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of G Protein Signaling 8 (RGS8) Requires Its NH2 Terminus for Subcellular Localization and Acute Desensitization of G Protein-gated K+ Channels

Abstract: Functional roles of the NH 2 -terminal region of RGS (regulators of G protein signaling) 8 in G protein signaling were studied. The deletion of the NH 2 -terminal region of RGS8 (⌬NRGS8) resulted in a partial loss of the inhibitory function in pheromone response of yeasts, although G␣ binding was not affected. To examine roles in subcellular distribution, we coexpressed two fusion proteins of RGS8-RFP and ⌬NRGS8-GFP in DDT1MF2 cells. RGS8-RFP was highly concentrated in nuclei of unstimulated cells. Coexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 27 publications
1
57
0
Order By: Relevance
“…A bioassay was used to measure the sensitivity of the pheromone response in yeast that expresses RGS proteins as described (6,12). As the expression level of RGS8 protein was not high enough in yeast, a sequence based on the Kozak consensus sequence and a N-terminus myc tag (MEQKLISEEDLSRGS) were fused to RGS8 or RGS8S cDNA to increase the expression level.…”
Section: Materials and Methods Reverse Transcriptase-pcr (Rt-pcr)mentioning
confidence: 99%
See 2 more Smart Citations
“…A bioassay was used to measure the sensitivity of the pheromone response in yeast that expresses RGS proteins as described (6,12). As the expression level of RGS8 protein was not high enough in yeast, a sequence based on the Kozak consensus sequence and a N-terminus myc tag (MEQKLISEEDLSRGS) were fused to RGS8 or RGS8S cDNA to increase the expression level.…”
Section: Materials and Methods Reverse Transcriptase-pcr (Rt-pcr)mentioning
confidence: 99%
“…Acute desensitization of GIRK current observed in the presence of RGS8, however, was not induced. Thus, we clarified that RGS8 requires its N terminus for subcellular localization and full regulatory function (6). On the other hand, Zeng et al (7) reported that the N-terminal domain (1-33 aa) of RGS4 confers receptor-selective inhibition of Gq signaling.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Closely related proteins like RGS7 and the RNA processing variant RGS9-2, are found in the cytoplasm or nucleus (16)(17)(18), as well as on plasma membranes. Other RGS proteins in general show highly varied distribution patterns (19)(20)(21)(22)(23)(24)(25)(26). Variable subcellular targeting of RGS proteins may be a mechanism for regulation of their functions (18,(27)(28)(29).…”
mentioning
confidence: 99%
“…Because receptor-G protein complexes are membrane bound, cellular mechanisms must direct RGS, usually confined away from signaling components (Hollinger and Hepler, 2002), to target G␣ subunits. Several RGS translocate to the plasma membrane (PM) when exposed to GTPase-deficient G␣ subunits or through mechanisms initiated by G protein activation (Druey et al, 1998;Saitoh et al, 2001). How RGS assemble with the signaling machinery in living cells is a highly debated issue (Hepler, 2003;Roy et al, 2003).…”
Section: Introductionmentioning
confidence: 99%